History of wolves : a novel - Fridlund, Emily (Atlantic Monthly Press, 2017)
"So delicately calibrated and precisely beautiful that one might not immediately sense the sledgehammer of pain building inside this book. And I mean that in the best way. What powerful tension and depth this provides!"-Aimee Bender. Fourteen-year-old Linda lives with her parents in the beautiful, austere woods of northern Minnesota, where their nearly abandoned commune stands as a last vestige of a lost counter-culture world. Isolated at home and an outlander at school, Linda is drawn to the enigmatic, attractive Lily and new history teacher Mr. Grierson. When Mr. Grierson is charged with possessing child pornography, the implications of his arrest deeply affect Linda as she wrestles with her own fledgling desires and craving to belong. And then the young Gardner family moves in across the lake and Linda finds herself welcomed into their home as a babysitter for their little boy, Paul. It seems that her life finally has purpose but with this new sense of belonging she is also drawn into secrets she doesn't understand. Over the course of a few days, Linda makes a set of choices that reverberate throughout her life. As she struggles to find a way out of the sequestered world into which she was born, Linda confronts the life-and-death consequences of the things people do-and fail to do-for the people they love. Winner of the McGinnis-Ritchie award for its first chapter, Emily Fridlund's propulsive and gorgeously written History of Wolves introduces a new writer of enormous range and talent"--